The Rasch Analysis of Rosenberg Self-Esteem Scale in Individuals With Intellectual Disabilities - Park, Ju-Young; Park, Eun-Young (Frontiers in Psychology, 2019)
Background: The purpose of this study was to examine the psychometric properties of the Rosenberg Self-Esteem Scale for individuals with intellectual disabilities using the Rasch model and to determine whether the scale is valid and reliable for use with this population. Methods: Rasch analysis was carried out on data from 223 respondents to the 8th Panel Survey on Employment for the Disabled conducted by the Korea Employment Agency for the Disabled. The validity and reliability of scale items were verified through analyses of item fit, item difficulties, the rating scale, and separation indices. Results: Item infit mean square values were found to range between 0.71 and 1.25, and item outfit mean square values between 0.71 and 1.26. Additionally, item difficulties were appropriate; Item 4 was the most difficult item, while Item 10 was the easiest item. The 4-point rating scale was appropriate, and the separation indices were at an acceptable level. Conclusions: Based on these results, the validity and reliability of the Rosenberg Self-Esteem Scale for use with individuals with intellectual disabilities were verified. Thus, this scale can be regarded as a useful tool for evaluating the level of self-esteem of individuals with intellectual disabilities.